The Monster Diaries - Saracino, Luciano (London : Parragon, 2012)
"Special memo from the Federation of Fright: Human children have run out of nightmares. There is a competition to find the Grisliest Ghoul. Top monsters willl study diary entries to determine the most fearsome fiend." Read the diary entries from witches, aliens, yetis, and more and find out who will win the grisliest ghoul competition!
M
b
b
Keywords: Monsters; Halloween; Horror